Dying at home in rural residential aged care: A mixed‐methods study in the Snowy Monaro region, Australia. (16th May 2018) - Rainsford, Suzanne; Phillips, Christine B.; Glasgow, Nicholas J.; MacLeod, Roderick D.; Wiles, Robert B.
Abstract: Residential aged care (RAC) is a significant provider of end‐of‐life care for people aged 65 years and older. Rural residents perceive themselves as different to their urban counterparts. Most studies describing place of death (PoD) in RAC are quantitative and reflect an urban voice. Using a mixed‐methods design, this paper examines the PoD of 80 RAC residents (15 short‐stay residents who died in RAC during respite or during an attempted step‐down transition from hospital to home, and 65 permanent residents), within the rural Snowy Monaro region, Australia, who died between 1 February 2015 and 31 May 2016. Death data were collected from local funeral directors, RAC facilities, one multi‐purpose heath service and obituary notices in the local media. The outcome variable was PoD: RAC, local hospital or out‐of‐region tertiary hospital. For the permanent RAC residents, the outcome of interest was dying in RAC or dying in hospital. Cross tabulations by PoD and key demographic data were performed. Pearson Chi squared tests and exact p ‐values were used to determine if any of the independent variables were associated with PoD. Using an ethnographic approach, data were collected from 12 face‐to‐face, open‐ended interviews with four RAC residents, with a life expectancy of ≤6 months, and six family caregivers. Interviews were audio‐recorded, transcribed and analysed thematically. Fifty‐one (78.5%) of the permanent residents died in RAC; 21.5% died in hospital. Home was the initial preferred POD for most interviewed participants; most eventually accepted the transfer to RAC. Long‐term residents considered RAC to be their "home"—a familiar place, and an important part of their rural community. The participants did not consider a transfer to hospital to be necessary for end‐of‐life care. Further work is required to explore further the perspectives of rural RAC residents and their families, and if transfers to hospital are avoidable.